Mixed method research designs: a case study of their adoption in a doctor of business administration program - Miller, P.; Cameron, Roslyn (Routledge, 2011)
The paper presents empirical data concerning the utilisation of mixed method research in Doctor of Business Administration (DBA) research projects (theses). The Southern Cross University, Australia, DBA program was established in 1996 as a research degree and has successfully graduated over 250 graduates from a diverse range of countries across the globe. It is the largest DBA program in the Australasia. The research will present prevalence rates of mixed methods research utilised by doctoralcandidates, data will be presented on the most frequently used data collection methods and research approaches within the field of business and management, with empirical data from a number of countries including Australia, Thailand, Malaysia, Singapore, and Indonesia. Emergent issues with regard to the use of mixed methods research in business and management research and the teaching of mixed methods are discussed.